A Comparison of the SAVI and VAK Learning Models on IPAS Learning Outcomes in Grade 5 - Aby Rafdi Auzan Ramadhan; Ika Yatri (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to compare the learning outcomes of fifth-grade students in Natural and Social Sciences (IPAS) taught using the Somatic, Auditory, Visual, Intellectual (SAVI) learning model and the Visual, Auditory, Kinesthetic (VAK) learning model. This study employed a quantitative approach with a quasi-experimental posttest-only design involving 64 fifth-grade students. The participants consisted of 32 students in the SAVI group and 32 students in the VAK group. Data were collected using a 25-item multiple-choice post-test and analyzed using the Rasch Model with the stacking technique using Winsteps version 4.8.2. The results showed that the mean measure of the SAVI group was 1.49 logits, whereas the VAK group achieved 1.67 logits, indicating a difference of 0.18 logits. Both learning models supported students' IPAS learning outcomes, with the VAK learning model demonstrating a higher mean measure than the SAVI learning model. These findings indicate that the VAK learning model is a promising alternative for supporting student-centered IPAS learning in elementary schools.